Hydroxyethyl Starch 130/0.4 and Its Impact on Perioperative Outcome: A Propensity Score Matched Controlled Observation Study. (June 2018) - Pagel, Judith-Irina; Rehm, Markus; Kammerer, Tobias; Hulde, Nikolai; Speck, Eike; Briegel, Josef; Reinholz, Falk; Crispin, Alexander; Hofmann-Kiefer, Klaus F.
Abstract : BACKGROUND: Adverse effects of hydroxyethyl starches (HESs) have been verified in patients suffering from sepsis or kidney disease, but not in surgical patients at large. The investigation aimed to determine whether the use of HES 130/0.4 was associated with the incidence of acute postinterventional adverse events compared to Ringer's acetate alone in a perioperative setting. METHODS: This propensity score matched, controlled observational study was performed in a single-centre university hospital. The perioperative data of 9085 patients were analyzed. Group matching was based on 13 categories including demographic data, type of procedure, and 5 preexisting comorbidities. Duration of procedure and intraoperative transfusion requirements were integrated in the matching process to reduce selection and indication bias. The primary outcome was incidence of postoperative kidney failure. Secondary outcomes were in-hospital mortality, fluid requirements, blood loss, hemodynamic stability, and the need for postoperative intensive care unit (ICU) treatment. RESULTS: The administration of HES 130/0.4 was not associated with an increased frequency of postoperative kidney failure. In-hospital mortality (Ringer's acetate: 2.58%; HES 130/0.4: 2.68%) and the need for ICU care (Ringer's acetate: 30.5%; HES 130/0.4: 34.3%) did not differ significantly between groups. Significant intergroup differences were observed for mean blood loss (Ringer's acetate: 406 ± 821 mL; HES 130/0.4: 867 ± 1275 mL; P < .001) and median length of hospital stay (Ringer's acetate: 10.5 (5/17) days; HES 130/0.4: 12.0 (8/19) days; P < .001). CONCLUSIONS: An association between intraoperative HES therapy and postoperative kidney failure was not observed in a mixed cohort of elective surgical patients. In addition, HES 130/0.4 was not associated with an increased morbidity or the need for ICU therapy in this propensity score matched study.